Assessment of Wildfire Vulnerability Using Satellite Image in the Michiquillay River Micro-watershed, Cajamarca - 2024 - Licapa-Redolfo, Gladys Sandi; Castillo Rios, Janeth Silvana; Díaz Rimarachín, Haydeé; Gastolomendo Malimba, Edilberto (LACCEI, 2025)
This study aimed to assess wildfire vulnerability in the Michiquillay River micro-watershed, Cajamarca – 2024, using remote sensing and geospatial analysis. Sentinel-2 imagery and spectral indices NDVI and NBR were employed to identify high-risk areas. The methodology included a multi-temporal analysis of satellite images from June, September, and November 2024, processed in ArcGIS Pro. The average NDVI was calculated at 0.4589, and the average NBR ranged from -0.092 to 0.3, both combined into a vulnerability index. Additionally, factors such as altitude (2,937 – 3,994 m.a.s.l.), annual precipitation (740 – 1,030 mm), and slopes greater than 27° were evaluated. Results showed that 32% of the area presents high or very high vulnerability, mainly concentrated in agricultural and pasture areas, whereas forested regions have lower risk due to higher moisture content. The study concluded that geospatial analysis effectively identifies critical areas and that the combination of NDVI and NBR is a reliable approach for assessing fire susceptibility. The findings will support the planning of wildfire prevention and risk management strategies in the Cajamarca region.